Model Pemberdayaan Guru Kelas Untuk Memfasilitasi Pembelajaran Siswa Broken Home Di Sd Negeri Rogomulyo 01 Kecamatan Kayen Kabupaten Pati 2016 - Rifani, Andy, Dr. Eko Supriyanto (2017)
Abstract This study aimed to describe the model, type and type as well as the results of teacher empowerment in facilitating student learning Broken Home SDN Rogomulyo Kayen District 01 District Pati. This research is a qualitative study used an ethnographic approach. The research was conducted on teacher's grade 3, grade 4 and grade 5, as well as religious teachers who deal directly with students with conditions of a broken home in SDN Rogomulyo Kayen District 01 District Pati. Methods of data collection used in-depth interviews, documentation, and observation. Based on the research that has been done, it can be concluded that: 1) the students broken home on the students at SDN Rogomulyo District 01 District Pati Kayen attributable to several factors, among others, death or divorce, divorce because of the economy. Students are generally broken home need assistance in learning. 2) Model empowering teachers through mentoring by teachers in facilitating student learning through mentoring broken home specifically in the classroom and at home in accordance with the directives of the meeting of teachers and principals in SDN father Rogomulyo 01. 3) Type of teacher empowerment involvement of student's broken neighborhoods home and teachers offering support students in learning to be important in order to boost students' motivation. Therefore, teachers attempted to active communication with relatives of children who are victims of a broken home. 4) In the implementation of learning assistance teacher's class also always provide motivation for students to improve their academic achievement. Especially for students belonging to the category of a broken home, the teacher emphasizes motivation as well as providing assistance to students in order not to feel inferior or insecure both in relationships at school and at home. Through the assistance of learning that has been done by teachers, students judged to have perseverance in better learning. Keywords: Empowerment, Facilitate Learning, Student Broken Home.